The Impact of Music in Memory - Musliu, Arian; Blerta Berisha; Arjeta Musaj; Diellza Latifi; Djellon Peci (European Journal of Social Science Education and Research, 2019)
A lot of research has been done on the effects of music and sounds on performance in many areas of study. However, there have been mixed results about what kind of effects music can have. Musical pleasure was able to influence task performance, and the shape of this effect depended on group and individual factor (Gold B., et al. 2013). According to Fassbender (2012), music does have an effect on memory, music during a study or learning phase hindered memory but increased mood and sports performance. The objective of this experiment is to find if music can help memorize different tests like nonsense syllables, numbers and poems with rhyme. Students were from different faculties, N=74 (75 percent females) between age 17-22, participating in this experiment. Experiment had 4 different tests, self-created according to the experiment of nonsense syllables from (Ebinghaus 1885). First test had 50 nonsense syllables to lead to the next phase of experiment. Students were separated in 3 groups with almost the same numbers of correct nonsense syllables from the first test. First group was taking the tests without music at all and in silent, second group was doing the test with lyrics music and the third group with relaxing music. All three groups had 5 minutes for each 3 different tests to memorize 50 other nonsense syllables (including 3 same syllables), 12 lines from poems and 50 different order of numbers, then to write down how much they memorized. The music was the same during memorizing phase and was repeated during writing phase with same volume and with headphones on. Result showed that there are significant differences memorizing lines from poems and the same syllables between students without music and them with music. T-test for each group also showed the significant differences between these two groups. Regression analyses explain 33 percent of variance factors for memorizing the lines and 50 percent of variance factors for memorizing the same syllables, groups have the most impact on regression. Conclusions of this research are that music affects memory negatively resulting that students are able to memorize better without music. This research also concludes that silent is a key factor to recognize the same nonsense syllables. When it comes to memorizing better keep the music down!
Keywords: Memory, music, memory tests, affect of music.